Microwave induced synthesis of magnetic biochar from agricultural biomass for removal of lead and cadmium from wastewater - Yap, M.W.; Mubarak, N.M.; Sahu, J.N.; Abdullah, E.C. (Elsevier, 2017)
The novel magnetic biochar (MB) has been successfully synthesized by using the microwave technique, using discarded materials such as coconut shell (CS). The optimized conditions for the best novel magnetic biochar synthesis are at 800 W reaction power, 20 min reaction time, and 0.5 g (FeCl3:biomass) impregnation ratio. The detailed physical and chemical analyses of novel magnetic biochar were found to be in good agreement with the hypothesis. These newly produced magnetic biochars have high surface area of 834 m2/g and this leads to high efficiency in the removal of cadmium and lead from wastewater. The results revealed that magnetic biochar composite exhibited excellent ferromagnetic property with a saturation magnetization of 6 emu/g. As for new invention, the magnetic biochar can be directly produced using microwaves heating by single stage of activation compared to the conventional method.